PENERAPAN ASAS BILATERAL DALAM KEWARISAN ISLAM MENURUT ULAMA SUNNI DAN SYI’AH IMAMIYYAH - Faisal Faisal (Jurnal AL-AHKAM, 2021)
The writing of this paper originates from the  difference  between  Sunni  inheritance  law  and  Shia  inheritance  law.  Sunni ulama prioritize  male  lineage relationships while Shia clerics prioritize closest kinship relationships. The problem in this study is why Sunni and Shia scholars have different opinions on the issue of bilateral implementation and what propositions are used by Sunni and Shia scholars and what are the implications of the differences in opinion between Sunni and Shia scholars. The aims of this research   are:   First,   to   see   why,   Sunni   and   Shia   scholars   differ   in   the implementation of the bilateral system in inheritance. Second, to understand the arguments that are used as references by Sunni scholars and Shia scholars. In this study, researchers conducted library research (library research) with informative data techniques that studied, analyzed and recorded all information obtained from various written documents, both primary and secondary. The result of the research shows that the implementation of the bilateral principle in inheritance law according to Sunnis and Shiites is very contradictory. For Sunni scholars, inheritance is only distributed based on dhaw al furud, if there is any remaining property it will be given to 'asabah. 'Asabah is an heir from the male path only so that in his distribution it is seen that there is still discrimination by women that had occurred before Islam entered. Meanwhile, Shia scholars in the distribution of inheritance emphasize kinship relations. The heir who has a very close relationship with the heir will take the inheritance and will veil the heir who only has close kinship. Male and female heirs have equal positions. Sunni scholars use the arguments contained in surah an-Nisa 'verse 11 and verse 12. In that verse the heir portion has been determined. Meanwhile, Shia scholars have a broad view of the Qur'anic verse. Especially with regard to kinship in Surah al-Anfal verse 75. This verse is actually used as the principle of inheritance in the Al-Qur'an.